SDG2 - Zero hunger : food security, improved nutrition and sustainable agriculture - Cheo, Ambe Emmanuel; Tapiwa, Kugedera Andrew (Concise guides to the UN Sustainable Development Goals., 2021)
SDG2 links food security, nutrition and a sustainable but climate resilient agriculture. This multi-dimensional goal encompasses several specific targets and indicators, aimed at ending hunger, improving nutrition and achieving food security through sustainable and resilient agriculture and income increase. This book assesses the implications of SDG2 for the economic, social and environmental domains of communities and countries. Three case study countries (Nigeria, Ghana, and The Gambia) were used to record values of their SDG2 indicators to demonstrate the operationalization of keeping track and measuring progress. This research shows that many of the datasets for the three countries are not available in the Global SDG Indicators Database compiled through the United Nations system. This book supports the database update process by United Nation Statistics Division since it enhances the process of proper accounting in reporting progress. Furthermore, the book supports the enhancement of the adaptive capacity and resilience of small-scale farmers since it is critical to reverse the trend in the rise in hunger. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.